FATF Recommendation and Charitable Organizations Supervision Policy in Indonesia: A Study on the Prevention of Terrorism Financing - Muslim, Fithriadi; Zulfa, Eva Achjani (UI Scholars Hub, 2025)
This research aims to analyze the supervision policies of charitable organisations in Indonesia, particularly in the context of preventing terrorism financing, and comparing them to international provisions, such as the Financial Action Task Force (FATF). It also explores the oversight practices in other countries to identify the best practices that Indonesia can adopt. The research addresses two key questions: (1) How do Indonesia’s supervision policies for charitable organisations prevent terrorism financing? (2) How do Indonesia’s supervision practices compare with international standards in preventing terrorism financing? This study uses a normative juridical approach, focusing on legislative and comparative methods. Primary legal sources include relevant laws and regulations, while secondary sources consist of literature reviews and prior studies. The research analyzes the phenomenon of charitable organisations being misused for terrorism financing and examines the ideal legal framework to prevent such misuse. FATF recommendations on Non-Profit Organisations (NPOs) serve as a benchmark for this analysis. The comparative aspect of this study provides insight into how other countries manage charitable organisations to mitigate the risk of terrorism financing. Insights from countries like the United Kingdom and United States highlight the importance of targeted outreach, mandatory audits, and advanced risk-based policies. Ultimately, this research proposes to integrate these practices into Indonesia’s supervision policies to enhance effectiveness, being aligned with FATF standards, and preserve the integrity of the charitable sector.